Basic Literacy Assistance at the Taman Baca Anak Merdeka - Ota, Maria Kristina; Amrin, Sayful; Ma, Stefanus H.G.; Parera, Helena Rosalia; Banda, Yosef Moan; Nande, Marsel; Djou, Ana Maria Gadi; Gaa, Yovita (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
Basic literacy is an ability that children must have from an early age, especially with increasingly developing technological developments; children must have good basic literacy skills. This mentoring activity aims to overcome the existing problem, namely that some children still need to be more active in reading and writing even though they have joined the Reading Park. The assistance provided is not only limited to reading and writing literacy but also numeracy literacy, scientific literacy, digital literacy, financial literacy and cultural literacy. It is done so that children in reading gardens do not feel bored with reading and writing with the same activities but are also allowed to learn other things. Apart from that, companions also provide educational games that can help motivate and entertain children. Educational games themselves cannot be separated from literacy activities. The implementation method is to apply the PALS (participatory action learning system) method. Some of the activities carried out in this mentoring provide very good benefits for the children. The children feel very motivated to continue moving forward and improve themselves to become better. The conclusion from this assistance is that children feel increasingly motivated and have quite a high interest in learning basic literacy and other forms of basic literacy as part of this assistance.